2016
DOI: 10.1007/s00167-016-4379-4
|View full text |Cite
|
Sign up to set email alerts
|

Blood supply of the subacromial bursa and rotator cuff tendons on the bursal side

Abstract: The subacromial bursa appears well vascularized. The results of the present investigation showed that blood supply to the subacromial bursa at the caudal part and rotator cuff tendons on the bursal side was linked to the same arteries. The subcoracoid artery supplied interval rotator structures close to the caudal bursa. It is the wish of the authors that this meticulous anatomical work will help surgeons in their day-to-day clinical work, e.g. to minimize the risk of complications such as perioperative bleedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…When compared to healthy bursae, tissue from the pathology groups 2–4 scored higher in the histological score classification system with respect to the number of fibroblasts, blood vessels and nerve fibers present. These results are in accordance with previous findings, showing that altered bursa tissue is well vascularized [ 12 ] and a rich source of cells such as fibroblasts, synoviocytes, endothelial cells and immune cells [ 13 , 29 ]. The present study supports the presence of leukocytes and monocytes/macrophages in bursae of pathological shoulders.…”
Section: Discussionsupporting
confidence: 93%
“…When compared to healthy bursae, tissue from the pathology groups 2–4 scored higher in the histological score classification system with respect to the number of fibroblasts, blood vessels and nerve fibers present. These results are in accordance with previous findings, showing that altered bursa tissue is well vascularized [ 12 ] and a rich source of cells such as fibroblasts, synoviocytes, endothelial cells and immune cells [ 13 , 29 ]. The present study supports the presence of leukocytes and monocytes/macrophages in bursae of pathological shoulders.…”
Section: Discussionsupporting
confidence: 93%
“…This is because the structural integrity and mechanical strength of injured rotator cuff tendon are far less than the original tendon. The underlying mechanism for this phenomenon is that the tendon lacks cells and blood supply and the regeneration ability is weak (Barile et al, 2017;Põldoja et al, 2017). Although physical methods can be used clinically, such as improving suture methods and knotting techniques to reduce the chance of suture prolapse (Kunze et al, 2020;Sundaram et al, 2020), only fundamental enhancement of regeneration ability of the rotator cuff tendon can make a big difference.…”
Section: Surgeries For Rotator Cuff Repairmentioning
confidence: 99%
“…4 This hypothesis has been contradicted in other studies, and a recent level 1 study has reported better outcomes with limited bursectomy. [5][6][7][8] The regenerative potential of subacromial bursal cells has been evaluated in basic science studies and the possible advantages of increased healing potential and better incorporation of the cuff at the tendonebone interface have been suggested. 2,3,9 The subacromial bursa extends from medial to lateral across the posterosuperior rotator cuff and is relatively thicker and structurally stronger medially and posteriorly.…”
Section: Pitfallsmentioning
confidence: 99%